Confirmación de presencia, registro de anidación, variación estacional de la densidad y uso de recursos para percha de la paloma turca (Streptopelia decaocto; Frivaldszky, 1838) en Morelia, Michoacán, México - Maya-Elizarrarás, Elisa; Maya-Elizarrarás, Luis Manuel (Instituto de Ecología, A.C., 2018)
The Eurasian-collared Dove (Streptopelia decaocto) is an invasive species in North America in the country process of active expansion. Their impact on native biodiversity and public health highlight the importance of knowing patterns of establishment (timing of establishment, population size and dispersion patterns), and potential biotic interactions with other species. We recorded use of perching substrates of the Eurasian-collared Dove density at the beginning and end of one reproductive season in Morelia, Mexico. We used variable-long transects to calculate Eurasian-collared Dove density, and recorded substrate used for each individual observed. Density did increase between survey seasons significantly, however, S. decaocto distribution inside the city was not homogeneous: 82% of records (56 individuals) were concentrated in only two transects. Furthermore, we documented significative change in Casuarina equisetifolia use as perching substrate between the beginning and the end of the reproductive season. Our observations also confirm that the Eurasian-collared Dove is stablished in Morelia city. It is crucial to enhance our knowledge of this exotic and invasive bird species at local scales in order to develop better control and/or eradication management practices.